Pengaruh Penggunaan Media Kantong Abjad Dalam Meningkatkan Kemampuan Mengenal Huruf Pada Anak Kelompok B di TK Negeri Terang Kabupaten Manggarai Barat Flores - Elviana; Ahmad Afiif; Muh. Anwar HM; Munawwir, Ahmad (NANAEKE: Indonesian Journal on Early Childhood Education, 2025)
This research aims: 1) To describe the ability to recognize letters before the application of alphabet pocket media to group B children at Terang state kindergarten west manggarai regency Flores; 2) To describe the ability to recognize letters after the application of alphabet pocket media to group B children at Terang state kindergarten west manggarai regency Flores; 3) To describe the effect of using alphabet pocket media on the ability to recognize letters in group B children at Terang state kindergarten west manggarai regency Flores. This research is a quantitativeresearch with a pre-experimental design approach with the type of design “One Group Pre-Test-Post-Test Designs”, The sampling technique used a saturated sampling technique so that the number of samples obtained was 12 children. The research instrument used was a guideline for observing the ability to recognize letters. Data analysis used in this study was a descriptive and inferential statistical analysis technique. The results of the study showed that: a) The use of alphabet pocket media before carrying out treatment, the average value of children’s ability to recognize letters obtaided was 11.08; b) The use of alphabet pocket media has proven effective in omproving the ability to recognize letters in children in group B. This can be seen after carrying out treatment 5 times, the average value is 18.41; c) Based on the results of the study, there is an effect of the use of alphabet pocket media on the ability to recognize letters in children in group B at TK Negeri Terang, west manggarai regency Flores.